Cinco formas de representar el pasado, a propósito de las polémicas en torno de Juárez (1905-1906) - Luna Argudín, María (El Colegio de México, A.C., 2008)
In the early twentieth century, Francisco Bulnes questioned the hegemonic representation of Benito Juárez. One of the answers was a literary contest to celebrate the first century of his birth. Rafael de Zayas Enríquez was rewarded for his biography, and Ricardo García Granados, Andrés Molina Enríquez and Porfirio Parra for their sociological studies of the Reform. This paper reconstructs the authors’ ennunciation horizon, analyzing specifically the ways of representing the past from the viewpoint  of history,  historical critique and sociology, as well as the uses of the past to diagnose national problems,  to reform the institutional framework and its political practices, and to create a homogeneous national identity.